Gender moderates the health-effects of job strain in managers - Gadinger, Michael Christian; Fischer, Joachim E.; Schneider, Sven; Terris, Darcey D.; Krückeberg, K.; Yamamoto, Shelby; Frank, Gunter; Kromm, Walter (International archives of occupational and environmental health, 2010)
To investigate cross-sectional associations between main, interactive and gender-dependent effects of the demand-control-support (DCS) model and subjective health in managers.
Online veröffentlicht am 4. November 2009
Gesehen am 24.07.2023